INCREASING SPEAKING SKILL THROUGH ROLE-PLAY AND STORY-TELLING AIDED WITH AUDIO-VISUAL - Budiarto Budiarto (STIBA IEC JAKARTA, 2019)
The aim of this study is to convey in-depth research on improving English speaking skills as integrated skills assisted by audio visual. This research includes; 1) the process of improving English speaking skills as an integrated skill assisted by audio visual, and 2) the results of improving English speaking skills as integrated skills assisted by audio visual. The research method used is action research that implements teaching that is considered capable of improving the learning process which is automatically expected to improve the results achieved by students. The research found that role-play and story-telling are techniques that can be used to teach speaking speaking. Role-play and story-telling will not run smoothly when the teacher intervenes students’ activities too much. Students need to work on their own to become autonomous and independent learners so that they will have lots of activities to communicate using English.